Research on Rural Heating Energy Reform in Heilongjiang Province: Based on a Survey of 209 Households - Lu Shuaijun; Liu Tiansen; Dong Mengtong; Wu Hanxue; Zhang Qiaowei (E3S Web of Conferences)
Since the 19th century, the continuous development of heavy industry in Northeast China has led to a yearly increase in emissions of carbon dioxide and other harmful substances, resulting in persistently high environmental pollution indices. This study collected 209 questionnaires by means of questionnaire method, and conducted descriptive analysis and empirical analysis based on the questionnaire to explore the core factors affecting the rural heating energy reform in Heilongjiang Province, and put forward conclusions and suggestions to promote the reform. By introducing indoor winter temperature(T) and annual heating expenditure(E) as independent variables and the heating technology rating(N) as a moderating variable Establish the regression equation, to exploring the influencing factors of heating satisfaction, the results reveals that villagers prefer heating methods that are environmentally friendly, easy to operate, and cost- effective. A Light GBM classification model further indicates that the promotion of clean-energy reform should not rely solely on economic subsidies but must also address public awareness and attitudes. Finally, Friedman and Wilcoxon signed rank tests were applied to examine key issues (Q) and government-driven optimization methods (V) for heating-energy structure, The results show that the government should focus on the economy, heating effect and environmental pollution of clean heating to avoid waste of resources.